A simple and highly reliable method to enhance the adhesion properties of polyethylene using Kapton-taping process. (October 2021) - Jeong, Sun Hwan; Heo, Jun Hyuk; Lee, Jin Woong; Cho, Hui Hun; Lee, Byoungsang; Lee, Jung Heon
Abstract: Although polyethylene (PE) is one of the most frequently used synthetic polymers in the plastics market, it is very difficult to imprint or bond PE with adhesives without pre-treatments based upon electrical, chemical and thermal processes. This is because a uniform adhesion property of PE cannot be expected without these processes. In this study, we suggest a simple, fast and cost-effective method to improve the adhesion properties of PE using a Kapton tape, which is a polyimide film generally used in flexible electronics. Specifically, by wrapping PE substrates applied with an adhesive using a Kapton tape and curing the sample using either a hot-press or a hot plate, the standard deviation of the shear strength decreased by 82.1% and 87.6%, respectively. To further improve the adhesion of PE substrates, we functionalized their surface using coupling agents, such as (3-glycidoxypropyl) methyldiethoxysilane and (3-aminopropyl) trimethoxysilane after an ultraviolet-ozone process. Using X-ray photoelectron spectroscopy and vacuum Fourier-transform infrared spectroscopy analysis, we proved that a significant improvement in the adhesion of PE occurred because of chemical crosslinking between either epoxy or amine groups functionalized on the PE substrates and epoxy-based adhesives comprising diglycidyl ether epoxy resin and triethylenetetramine hardener. This study is important, as it suggests a simple and very effective method to obtain highly reliable adhesion properties of PE using conventional adhesives. Graphical abstract: Kapton-taping can be a simple, yet very effective, method to achieve highly reliable adhesion properties of polyethylene substrates with conventional adhesives, resulting in a significant decrease in the standard deviation of shear strength, in comparison to other curing methods, such as hot plate and hot-press. Image 1 Highlights: We demonstrated a method to improve the adhesion properties of polyethylene by simply wrapping samples using a Kapton tape. Kapton taping method significantly lowered the standard deviation of the shear strength. Functional groups that can be crosslinked with the main components of the adhesive greatly improved the adhesive properties. The ultraviolet-ozone treatment was necessary for facile modification of coupling agents on bare PE surface.